2022
DOI: 10.1139/cjp-2021-0361
|View full text |Cite
|
Sign up to set email alerts
|

Thermal diffusion effect on unsteady MHD free convective flow past a semi-infinite exponentially accelerated vertical plate in a porous medium

Abstract: The objective of the present work is to obtain an exact solution to the problem of a free convective, radiative, viscous, chemically reacting, heat absorbing, incompressible, and unsteady MHD flow past an exponentially accelerated moving vertical plate embedded in a porous medium. The fluid is assumed to be optically thick and non-gray. A magnetic field is applied in the transverse direction of the flow. Effects of arbitrary ramped temperature and thermal diffusion are also considered. Rosseland approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…They showed that the effect of thermophoresis could be quite significant in appropriate situations and that the number of undulations could essentially modify the heat transfer rate and fluid flow intensity. More recently, Sarma and Ahmed [18] investigated the thermal diffusion effect on unsteady MHD free convective flow past a semiinfinite exponentially accelerated vertical plate in a porous medium. The influence of physical parameters on flow and transport characteristics was analyzed with suitable graphs.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the effect of thermophoresis could be quite significant in appropriate situations and that the number of undulations could essentially modify the heat transfer rate and fluid flow intensity. More recently, Sarma and Ahmed [18] investigated the thermal diffusion effect on unsteady MHD free convective flow past a semiinfinite exponentially accelerated vertical plate in a porous medium. The influence of physical parameters on flow and transport characteristics was analyzed with suitable graphs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years several analytical methods for solving the non-linear differential problem have been used to model the heat and mass transfer in a viscous fluid/nanofluid flow [1][2][3][4][5][6][7] were applied.…”
Section: Introductionmentioning
confidence: 99%
“…The mass transfer of a chemically reactive species and the flow of MHD over a stretching plate subjected to an inclined magnetic field were examined by Maranna et al [2]. Sarma et al [3] explored the exact solution to the problem of a free convective, radiative, viscous, chemically reacting, heat absorbing, incompressible, and unsteady MHD flow using the Laplace transformation technique.…”
Section: Introductionmentioning
confidence: 99%